Characteristics, Functional Properties, and Antioxidant Activities of Water-Soluble Proteins Extracted from Grasshoppers,Patanga succinctaandChondracris roseapbrunner - Niphattha Chatsuwan; Sitthipong Nalinanon; Yuporn Puechkamut; Buddhi P. Lamsal; Praphan Pinsirodom (My University, 2018)
Water-soluble proteins extracted from two species of grasshoppers, Patanga succincta (WSPP) and Chondracris roseapbrunner (WSPC), were characterized as well as their functional properties and antioxidant activities were investigated. The extraction yield, on a wet weight basis, was 7.35% and 7.46% for WSPP and WSPC , respectively. The most abundant amino acid in both proteins was glutamic acid, followed by aspartic, alanine, and leucine, in that order. The electrophoretic study revealed that proteins with MW of 29, 42, 50, 69, and 146 kDa were the major protein components in WSPP and WSPC. FTIR analysis showed that those proteins remained their structural integrity. The surface hydrophobicity at pH 7 of WSPC was higher than WSPP, but the sulfhydryl group content did not show significant difference between the proteins from two species. Both grasshopper proteins were mostly soluble in strong acidic and alkaline aqueous solutions with a minimum value at pH 4. Those proteins exhibited poor emulsifying properties and foaming capacity, but they had greater foaming stability compared with bovine serum albumin (BSA) (p<0.05). WSPC showed greater DPPH • and ABTS •+ scavenging activities and ferric-reducing antioxidant power (FRAP) than did WSPP (p<0.05). Therefore, based on characteristics and functional properties, water-soluble proteins from both edible grasshoppers can be used as an ingredient in food applications.
Keywords: ABTS; Insect Utilization and Effects